Analysis of a vowel database - Assmann, Peter F.; Nearey, Terrance M.; Bharadwaj, Sneha (Canadian Acoustics, 2008)
The perceptual effects of upward and downward scaling of the formats in combination with changes in geometric mean fundamental frequency was investigated. A database of recordings from adults and children from the Dallas, Texas region was collected. A systematic relationship between the geometric mean of the format frequencies across all of the vowels for a given speaker and the geometric mean fundamental frequency was found. Vowels were recorded in hVd words, both in isolation and in a carrier sentence. Recordings were carried out over a 2.5-year period at the University of Texas at Dallas. Each recorded token was produced following a screen prompt that displayed the orthographic representation of the hVd word or sentence, along with an audio example spoken by an adult female from the Dallas area. It was observed that the geometric mean increases linearly with the geometric mean of the formant frequencies when data for males and females are combined.